Weight maintenance over 12 months after weight loss resulting from participation in a 12‐week randomised controlled trial comparing all meal provision to self‐directed diet in overweight adults. Issue 4 (18th November 2013) - Whitham, C.; Mellor, D. D; Goodwin, S.; Reid, M.; Atkin, S. L.
Abstract Background The results of weight maintenance after initial weight loss are reported infrequently, although, when they have been reported, the outcomes are generally poor and weight regain is common. Methods After an initial 12‐week randomised intervention comparing all meal provision against a self‐directed energy restriction, participants re‐consented to participate in a follow‐on study. Participants were given the option to choose to continue with the same dietary intervention (either all meal provision (provided free of charge) or self‐directed diet) or change to the other diet for a further 12 weeks. Participants were followed up at 4‐weekly intervals during both intervention periods (a total of 24 weeks), with a final follow up at 12 months. Results Eighty‐five out of 86 individuals who completed the original 12‐week randomised phase chose to continue on to the follow‐up study. No significant differences in further weight loss between groups (P = 0.138) [mean (SEM): −3.4% (1.1%) for all meal provision only; −3.4% (0.6%) self‐directed then all meal provision; −1.1% (1.2%) all meal provision then self‐directed] were seen after a further 12 weeks. Meal provision for a total of 24 weeks resulted in 67% of individuals losing at least 10% body weight. The groups switching from self‐directed dieting to meal provision (or vice versa) were the only groups to have a lower mean weight at 12 months than at the start of the follow‐on study. Conclusions Structured support for 24 weeks followed by 28 weeks of self‐care can result in weight maintenance, with initial weight loss maintained at 12 months from enrolling on a 12‐week weight loss intervention, with a 12‐week follow‐on period.